Pembelajaran Sosial Emosional di Sekolah Dasar - Dwi Rahayu Murtiningsih (Jurnal Pendidikan Tuntas, 2025)
This study discusses the importance of implementing Social, and Emotional Learning (SEL) at the Elementary School level as a foundation for holistic character development and student competency. The purpose of this study is to identify and analyze the concept, implementation, and impact of social emotional learning in the elementary school environment. This study uses a literature review method with a content analysis approach and narrative synthesis of various academic literature, including journals, books, and relevant research reports. The results of the study indicate that SEL makes a positive contribution to the development of social skills, emotional management, increased empathy, and increased student academic achievement. In addition, the success of SEL implementation is influenced by teacher support, an integrated curriculum, and a conducive learning environment. This study concludes that systematic integration of SEL in learning in elementary schools is very important for forming students' emotionally and socially balanced personalities. The implications of this study point to the importance of teacher training and the formulation of educational policies that support the sustainable implementation of SEL.